UNIFORM DISTRIBUTION EVALUATION OF ERBIUM IONS ALONG PREFORMS OF ACTIVE OPTICAL FIBER ACCORDING TO THE LUMINESCENCE INTENSITY AT DIFFERENT WAVELENGTHS - Latkin, K.P.; Smirnov, A.S.; Konstantinov, Yu.A.; Burdin, V.V. (Perm Federal Research Centre Journal, 2016)
Active optical fibers are widely used as the active medium in the optical fiber amplifiers and fiber lasers. The main parameter of active fibers, directly affecting the characteristics of lasers and amplifiers, is the concentration of active ions in the fiber core. The concentration of active ions in the fiber directly depends on the concentration of active ions in the preform from which the fiber is produced. To determine the active ion concentration uniformity in the preform the method of recording the luminescence spectrum of the active ions in sections along the preform is used. The pump radiation goes to core through the side surface of the preform. Erbium doped preforms are considered. In this paper we studied two preforms obtained by different methods: by impregnation with the liquid erbium compound and by modified chemical vapor deposition (MCVD). This paper deals with the determination of the active erbium ions concentration uniformity, based on the different intensities of wavelengths of the luminescence spectrum. The pumping is performed at a wavelength of 980 nm. The paper presents calculations of mutual correlation coefficients between the intensity distribution at the wavelength of maximum signal and intensity distribution at other wavelengths of the luminescence spectrum.